FAKTOR PENYEBAB STUNTING PADA BALITA USIA 1-5 TAHUN DI WILAYAH KERJA PUSKESMAS MPUNDA TAHUN 2021 - yubiah, tri (Jurnal Ilmiah Bidan (JIB), 2022)
This study aims to determine the causes of stunting in toddlers aged 1-5 years in the work area of ​​the MPunda Health Center in 2021. This study is a quantitative analytical study with the method used, namely an analytical survey to respondents to determine the factors causing stunting in toddlers aged 1-5 years. . The population in this study was 71 people, the sampling technique used was simple random sampling. The results of the study based on the pattern of parenting feeding the dominant toddler in the good category as many as 39 respondents (54%), based on the dominant mother's education in the mother with a high school education as many as 33 respondents (46%), based on the dominant economic level in the mother with a low economy as many as 48 respondents (68%). It is hoped that this research can be used as a basic material in policy making by the province